2022
DOI: 10.3390/medicina58020244
|View full text |Cite
|
Sign up to set email alerts
|

Eradication of Isolated Para-Aortic Nodal Recurrence in a Patient with an Advanced High Grade Serous Ovarian Carcinoma: Our Experience and Review of Literature

Abstract: We report a case report regarding the eradication of isolated lymph-nodal para-aortic recurrence in the aortic region down the left renal vein (LRV) in a patient treated two years earlier in another hospital for a FIGO stage IC2 high-grade serous ovarian carcinoma with a video showing the para-aortic space after eradication of the metastatic tissue. A 66 year-old woman was admitted 24 months after the initial surgical procedure for an increased Ca 125 level and CT scan that revealed a 3 cm para-aortic infraren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…No complication occurred in our patients intraoperatively and only 11.1% of our patients experienced grade 2 and 3 postoperative complications. These rates are similar and even lower than those reported in other studies [5,23,35]. Notably, all the patients with ILNR were successfully treated with a minimally invasive approach.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…No complication occurred in our patients intraoperatively and only 11.1% of our patients experienced grade 2 and 3 postoperative complications. These rates are similar and even lower than those reported in other studies [5,23,35]. Notably, all the patients with ILNR were successfully treated with a minimally invasive approach.…”
Section: Discussionsupporting
confidence: 83%
“…Particularly, several studies showed better outcomes in patients with ILNR undergoing secondary cytoreductive surgery in comparison with patients who underwent other treatments, such as salvage chemotherapy or the irradiation of bulky nodes. For example, Ferrero et al reported the feasibility of SCS for ILNR, achieving complete cytoreduction in 72 out of 73 cases, without significant morbidity, and a 5-year post-recurrence survival of 64% [5,35]. The quality of evidence in ovarian cancer recurrence treatment by MIS is low, being based mainly on case reports and retrospective studies with small sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical excision is its key therapy. Follow-ups through imaging (preferable MRI) are highly suggested to recognize recurrence and treat it promptly, with an attention comparable to other oncological conditions subjected to recurrence [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…15,16 The most common sites of relapses are pelvis and abdomen, whereas recurrence confined solely to lymph node is a rare event, accounting for 1-6%. 17,18 The treatment of choice for cases with isolated lymph node relapse (ILNR) has not been established yet in the literature due to heterogeneity of medical history and performance status of the patients, the evolution of chemotherapy agents, and the different sites of nodal disease among the cases. For instance, in a recent series of 79 patients, the treatment of ILNR included chemotherapy alone for 52 (65.7%) patients, surgery alone for 2 (2.5%) patients, the combination of surgery followed by chemotherapy for 17 (21.5%) patients and the combination of chemotherapy and radiotherapy for one patient (1.3%).…”
Section: Discussionmentioning
confidence: 99%
“…20 It is well mentioned that secondary debulking surgery in patients with paraaortic relapse includes high risks of iatrogenic vascular injuries due to their position posterior the major vessels. 18 Recent study pointed out that ILNR show better prognosis than disease relapse in other sites resulting in a median post-recurrence survival (PRS) rate of approximately 37 months and an OS rate of 109 months. 21 The recent study demonstrated significantly higher rates of overall survival (OS) and post relapse survival (PRS) in the retroperitoneal recurrence group compared to the intraperitoneal and combined site recurrence groups.…”
Section: Discussionmentioning
confidence: 99%